Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/axioms11030135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Term Structure of Major Currencies Using Principal Component Analysis and Autoencoders

Abstract: Recently, machine-learning algorithms and existing financial data-analysis methods have been actively studied. Although the term structure of government bonds has been well-researched, the majority of studies only analyze the characteristics of one country in detail using one method. In this paper, we analyze the term structure and determine the common factors using principal component analysis (PCA) and an autoencoder (AE). We collected data on the government bonds of three countries with major currencies (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The Model Classifier can be trained and tested using the output. An autoencoder was used to extract the dimensions, after which they were converted into features for 27,26,25,24,23,22,21,20,19,18,14,10, and 6 neurons. The Autoencoder (AE) model is configured with the activation function at the bottleneck, encoder 1, encoder 2, decoder 1, and encoder 2 using Relu, the kernel initializer used is Random Normal with a standard deviation of 0.01, the initializer bias used is Zeros, and linear activation is used on the output layers.…”
Section: Architecture Of the Autoencodermentioning
confidence: 99%
See 1 more Smart Citation
“…The Model Classifier can be trained and tested using the output. An autoencoder was used to extract the dimensions, after which they were converted into features for 27,26,25,24,23,22,21,20,19,18,14,10, and 6 neurons. The Autoencoder (AE) model is configured with the activation function at the bottleneck, encoder 1, encoder 2, decoder 1, and encoder 2 using Relu, the kernel initializer used is Random Normal with a standard deviation of 0.01, the initializer bias used is Zeros, and linear activation is used on the output layers.…”
Section: Architecture Of the Autoencodermentioning
confidence: 99%
“…Inputs in autoencoder can be reconstructed effectively with minimum reconstruction error [25]. Some researchers use autoencoder as a learning feature because it performs both linear and non-linear projections and outperforms PCA in the processing of complex, highdimensional datasets [26], [27]. Akkalakshmi [28], using Autoencoder in predicting cancer disease to determine latent features.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prediction of financial assets remains a critical topic within financial mathematics. Recent studies have demonstrated the remarkable performance of Artificial Neural Network (ANN)-based machine learning methodologies in predicting future data (Casado-Vara et al [14], Chae and Choi [15], Lin et al [16]). Our study takes an effective approach by utilizing the LSTM methodology to forecast the price of the S&P 500, contributing substantially to the growing body of knowledge in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional mathematical and statistical methods, machine learning models have been shown in multiple research studies to have better predictive accuracy (Kim et al [20], Shin et al [21], Grendas et al [22], Chae and Choi [23]). As a result, we have chosen to use the SHAP-XGBoost algorithm to predict stock prices for K-Pop entertainment companies.…”
Section: Introductionmentioning
confidence: 99%